2022
DOI: 10.1186/s12961-022-00817-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased use of knowledge translation strategies is associated with greater research impact on public health policy and practice: an analysis of trials of nutrition, physical activity, sexual health, tobacco, alcohol and substance use interventions

Abstract: Background Greater use of knowledge translation (KT) strategies is recommended to improve the research impact of public health trials. The purpose of this study was to describe (1) the research impact of setting-based public health intervention trials on public health policy and practice; (2) the association between characteristics of trials and their research impact on public health policy and practice; and (3) the association between the use of KT strategies and research impacts on public hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 53 publications
(50 reference statements)
3
9
0
2
Order By: Relevance
“…There is an extensive variety of available dissemination channels and mediums, and many of the studies included in this scoping review utilised multiple channels. Not surprisingly, methods targeted at fellow researchers such as peer reviewed articles and conferences were one of the most common cited channels, as well as training/workshops/presentations, which is consistent with other studies that have explored dissemination strategies utilised by researchers [ 84 ]. The decision of which channel/s to use is informed by a number of factors including cost, familiarity, access, experience, as well as other components of dissemination such as the target audience and the source [ 85 ].…”
Section: Discussionsupporting
confidence: 81%
“…There is an extensive variety of available dissemination channels and mediums, and many of the studies included in this scoping review utilised multiple channels. Not surprisingly, methods targeted at fellow researchers such as peer reviewed articles and conferences were one of the most common cited channels, as well as training/workshops/presentations, which is consistent with other studies that have explored dissemination strategies utilised by researchers [ 84 ]. The decision of which channel/s to use is informed by a number of factors including cost, familiarity, access, experience, as well as other components of dissemination such as the target audience and the source [ 85 ].…”
Section: Discussionsupporting
confidence: 81%
“…The authors found that researchers reported more passive than active dissemination of their research, with this particularly evident among basic science researchers. Similar ndings have emerged in other surveys of researchers working in health-related elds, with more reporting using mostly passive diffusion strategies, including academic journals (88-99%) and academic conferences (90-93%) than active tailored approaches, such as plain language summaries (33-64%) and face-to-face meetings (48-68%) (13)(14)(15)(16). A 2012 survey study (17) found that only one-third of US-based health researchers involved endusers in their research.…”
supporting
confidence: 78%
“…systemach składających się z wielu elementów, między którymi zachodzą różne interakcje [34,35]. Należy podkreślić, że rozpowszechnienie wyników interwencji zdrowia publicznego, nawet gdy pokazują zaledwie względne korzyści (a także ich brak) jest istotnym wkładem do rozwoju wiedzy i podejmowania bardziej rygorystycznych metod badawczych [36].…”
Section: Podłoże Translacji Wiedzyunclassified